Evaluation Of Tourism Object Development Of Bukit Kandis In Central Bengkulu Regency - Imanda, Antonia; Saputra, Harius Eko; Jennifer, Cinthya (Journal of Research in Social Science and Humanities, 2021)
Bengkulu Province in resolving land disputes, focusing on mediation as a non-litigation dispute resolution mechanism. Land disputes in the region are triggered by various factors such as public ignorance of legal land status, low legal literacy, and weak land administration systems. Mediation is considered an effective method as it offers a faster and more amicable solution than formal litigation, emphasizing mutual agreement and efficiency. The research applies a juridical-empirical approach and descriptive qualitative method. Data were collected through interviews, literature review, and document analysis. The findings reveal that BPN acts not only as a neutral mediator but also as a legal educator and facilitator in clarifying land ownership issues. Despite these efforts, the implementation of mediation still faces significant challenges, including the absence of standardized technical guidelines, a lack of certified mediators, and limited public engagement. Therefore, this study recommends that BPN enhance its human resource capacity in mediation, develop clear and standardized procedures, and conduct ongoing public outreach and legal education campaigns. Strengthening these aspects is essential for positioning land mediation as an effective tool in achieving social justice and legal protection in the agrarian sector.